Rock Crushing Analysis of TBM Disc Cutter Assisted by Ultra-High-Frequency Loading - Zhao, Dajun; Han, Junpeng; Zhou, Yu; Lv, Xiaoshu; Zhang, Shulei; Gao, Ke; Zhao, Yan (Shock and vibration, 2022)
In the construction of mountain tunnels, the increasing proportion of hard rock stratum enhances the difficulty of rock breaking by tunnel boring machine (TBM). As a type of cyclic load with ultrahigh frequency, ultrasonic vibration has the advantages of energy concentration and strong penetration. In the process of rolling and extrusion, the weakening of the rock by ultrahigh-frequency loading can improve the rock crushing efficiency of the TBM disc cutter. In this study, we established a physical model of rock cutting using a disc cutter assisted by ultrasonic vibration and obtained a motion equation. The discrete element software particle flow code (PFC) was selected to construct a heterogeneous granite model to demonstrate the mechanism and development of cracks inside the hard rock under a rolling disc cutter assisted by ultrasonic vibration. The results demonstrate that ultrasonic vibration helps the disc cutter construct a stronger stress field in the shallow layer, which promotes tensile damage of the surface rock. Vibration promotes the development of cracks inside the rock and accelerates the penetration of transverse cracks, which is conducive to the stripping of rock fragments. The addition of ultrahigh-frequency loading also reduces the fluctuation increase of cracks, which makes the operation state of the disc cutter more stable and avoids abnormal damage to tools.